Faktor-faktor yang Berhubungan dengan Keluhan Dermatitis Kontak Iritan pada Pekerja Bagian Produksi dan Laboratorium PT. X - Triana Defani; Hendra Dhermawan Sitanggang; David Kusmawan; Willia Novita Eka Rini; Budi Aswin (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Irritant contact dermatitis is a skin disease that often occurs in rubber company workers due to contact with irritant materials. Irritant materials in the work environment can damage the skin, cause inflammation, and cause irritation. If not treated immediately, this condition can interfere with comfort and reduce work efficiency. This study aims to determine the factors associated with complaints of irritant contact dermatitis in production and laboratory workers at PT. X. This study uses a quantitative approach with an observational cross-sectional design. The study population was 64 workers, with 38 people as samples taken using a purposive sampling technique. The variables studied included the dependent variable (complaints of irritant contact dermatitis) and independent variables (length of service, exposure to chemicals, duration of exposure, personal hygiene, and use of PPE). Data analysis was carried out univariately and bivariately using the Chi-Square statistical test with a 95% confidence interval. The results showed that complaints of irritant contact dermatitis with moderate and severe categories were 44.7%, and the mild category was 55.3%. There was a significant relationship between length of work (p=0.031), length of exposure (p=0.032), personal hygiene (p=0.011), and use of PPE (p=0.024) with complaints of irritant contact dermatitis. Keywords:, ,